2014
DOI: 10.1155/2014/792569
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Stellate Ganglion Block in Postmastectomy Pain Syndrome: A Comparison of Ketamine versus Morphine as Adjuvant to Bupivacaine

Abstract: Background.The postmastectomy pain syndrome (PMPS) is chronic pain after breast cancer surgery and is reported to influence quality of life. The aim of this study was to provide long term reduction of PMPS, improve range of motion of the shoulder, and decrease the need for postoperative analgesia using ultrasound guided stellate ganglion block.Method.Sixty patients with PMPS were randomly allocated into 1 of 3 groups: bupivacaine group (group 1), bupivacaine plus ketamine group (group 2), and bupivacaine plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The only other study of PMPS treatment with SGB emphasized the efficacy of SGB with bupivacaine plus ketamine compared to bupivacaine alone or bupivacaine with morphine [21]. In this study, the bupivacaine plus ketamine group demonstrated decreased pain scores up to three months following the procedure, improved mobility, and decreased need for other analgesic drugs [21].…”
Section: Regional Anesthesiamentioning
confidence: 67%
See 1 more Smart Citation
“…The only other study of PMPS treatment with SGB emphasized the efficacy of SGB with bupivacaine plus ketamine compared to bupivacaine alone or bupivacaine with morphine [21]. In this study, the bupivacaine plus ketamine group demonstrated decreased pain scores up to three months following the procedure, improved mobility, and decreased need for other analgesic drugs [21].…”
Section: Regional Anesthesiamentioning
confidence: 67%
“…Patients still required morphine for pain control suggesting incomplete blockade of the upper limb; however, the pain remained decreased three months after treatment at vertebral levels T1-T4, suggesting effective analgesia at higher vertebral levels [19]. The only other study of PMPS treatment with SGB emphasized the efficacy of SGB with bupivacaine plus ketamine compared to bupivacaine alone or bupivacaine with morphine [21]. In this study, the bupivacaine plus ketamine group demonstrated decreased pain scores up to three months following the procedure, improved mobility, and decreased need for other analgesic drugs [21].…”
Section: Regional Anesthesiamentioning
confidence: 99%
“…On reviewing the literature, we found that SGB was tried for treatment of adhesive capsulitis of the shoulder with some success. 3 Abdel Dayem et al 10 found significant improvement in pain from 7.6±0.7 to 1.3±0.7 after three months of SGB injection with ketamine as adjuvant to bupivacaine and also found significant improvement in range of motion of shoulder after injection. In addition, there are several studies confirming these findings.…”
Section: Discussionmentioning
confidence: 96%
“…The SGB was repeated three times at one week intervals between each injection. 10 Group B (n=32) patients received ultrasound guided SGB using ketamine and bupivacaine in the same dose and intervals as group A plus posterior approach shoulder injection with PRP (3 times with 1 week interval). Opaque sealed envelopes technique was used for allocation concealment.…”
Section: Randomizationmentioning
confidence: 99%
“…PMPS first by reported by Wood in late 1970, and then Folly et al described PMPS as pain and sensory disorders following mastectomy. Post-mastectomy pain syndrome is described as a chronic neuropathic pain which caused by damage of the multiple nerves, and occurred after all types of breast cancer surgery (radical mastectomy, modified radical mastectomy, and lumpectomy associated with axillary lymph node dissection) [22]. It represents about 25%-60% of patients suffer from chronic pain after breast cancer-related surgery ( Figure 1) [23].…”
Section: Post Mastectomy Pain Syndrome (Pmps)mentioning
confidence: 99%